THE EFFECT OF DIFFERENT pH ON THE ACTIVITY OF THE CRUDE EXTRACT OF PROTEASE ENZYMES FROM THE VISCERA OF CATFISH (Pangasius hypophthalmus) - Illahi, Sikarina; Ilza, Mirna; Diharmi, Andarini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
Abstract                        The viscera of catfish are a by-product in the processing of catfish that have not been utilized optimally. The viscera of catfish can be used as raw material for enzymes. The viscera of catfish are thought to contain protease enzymes. This study aimed to determine the activity of crude extract of protease enzymes from the viscera of catfish (P. hypophthalmus) at different pH. The research was conducted through the sample preparation process, extraction of protease enzymes, measurement of enzyme activity in crude extracts of protease enzymes at different pH. The results showed that the activity value of the crude extract of the protease enzyme from the viscera of catfish (P. hypophthalmus) at pH 7; 8; 9 were 0.35 U/mL, 0.38 U/mL and 0.37 U/mL, respectively. The results showed that at pH 8 there was the highest activity value of the crude extract of the protease enzyme from the stomach contents of catfish (P. hypophthalmus).Keywords:catfish, pH,  protease enzyme,